Helicobacter Pylori Infection in Humans: Emerging Resistance Patterns, Diagnostic Challenges, and Novel Therapeutic Strategies - Manthor, Zainab Hakim Wannas; Jabr, Zahraa Hassan Farhan; Rashid, Tabarak Ali Hamid; Khames, Melad Yahya Saba; Husaen, Zhian Ramadhan Kyani (American Journal of Biology and Natural Sciences, 2025)
Helicobacter pylori (H. pylori) is a microaerophilic, spiral-shaped, gram-negative bacterium that primarily colonizes the gastric epithelium and is opportunistically responsible for chronic gastritis, peptic ulcer disease, mucosa-associated lymphoid tissue lymphoma, and gastric cancer. The human gut plays host to a broad-spectrum microbiome that is considered to be a critical factor in maintaining gut health and stability. However, H. pylori is one of the few bacterial species that can colonize the acid-secreting stomach, where it faced highly acidic conditions in the gastrointestinal tract. H. pylori infection is one of the most prevalent global chronic bacterial infections and is classified as a group I carcinogen. The overall prevalence of H. pylori infection is extremely high globally, posing a global health threat. H. pylori has been prioritized as a priority pathogen due to the increasing prevalence and the growing burden of antibiotic resistance. There is a critical shortage of treatment options for H. pylori infections that are not adequately addressed in the immediate to medium-term. New antibiotics with novel mechanisms of action are urgently needed to meet this challenge. H. pylori was discovered in 1982, and a rapid change has occurred in a remarkably short time. Since the introduction of combination therapies consisting of at least one antimicrobial agent and a proton pump inhibitor, H. pylori infection has been effectively treated for over 30 years. The development of antibiotic resistance patterns and shifts in sensitivity to first-line antibiotics are becoming a major concern in H. pylori eradication. The concomitant use of multiple antibiotics contributes to the emergent resistance patterns. Antibiotic resistance patterns in H. pylori are evolving. In this review, the current treatment options in eradicating antibiotic-resistant H. pylori are discussed. In addition, future perspectives such as diagnostic challenges and therapeutic strategies to combat antibiotic-resistant H. pylori are emphasized. H. pylori colonizes almost 50% of the world population and is the most common chronic infection in humans. Infection with H. pylori results in both acute and chronic gastric inflammation and a marked increase in the risk of developing severe gastric diseases including peptic ulcers, gastric cancer, gastric mucosa-associated lymphoid tissue lymphoma, and atrophic gastritis. H. pylori primarily colonizes the gastric epithelium and remains one of the only known bacterial species that live in the acidic compartment of the mammalian and avian stomach. It induces chronic gastric inflammation in almost all infected individuals, and 10% will develop severe gastric diseases.